Power and change: Locating institutional change theories in a power context - Lily Salloum Lindegaard (Danish Institute for International Studies (DIIS), 2013)
This working paper aims to better understand the drivers of institutional change. To do this, it locates diverse institutional change theories, specifically path dependency, gradual institutional change and institutional bricolage, in a power context and reflects on the power-related aspects of each theory. It then develops a novel approach of a power analysis of institutional change, which allows for the combined use of institutional change theories despite their diverse theoretical underpinnings and thus offers a thorough, highly complex consideration of institutional change.
Keywords: 300